Public relations in global culture contexts : multi-paradigmatic perspectives - Bardhan, Nilanjana; Weaver, C. Kay , 1964- (Communication series, 2011)
Providing a critical examination of public relations' contribution to globalization and international power relations, this title includes chapters that explore alternative paradigms, most notably interpretive and critical perspectives informed by qualitative research. It is suitable for students as well as practitioners of public relations